Yersinia specific immune complexes in the synovial fluid of patients with yersinia triggered reactive arthritis. Issue 7 (July 1987) - Lahesmaa-Rantala, R; Granfors, K; Isomäki, H; Toivanen, A
Abstract : Yersinia specific immune complexes were demonstrated in the synovial fluid of three patients out of 12 with yersinia triggered reactive arthritis. They were not detectable in the synovial fluid of any of the 16 control patients, including nine with reactive arthritis triggered by factors other than yersiniae. Platelet reactive IgG was detectable in the synovial fluid of eight out of the 12 patients with yersinia triggered reactive arthritis and in three of the 16 control patients, all three having rheumatoid arthritis. An enzyme linked immunosorbent assay and a platelet 125I labelled staphylococcal protein A test were used to measure yersinia specific immune complexes and platelet reactive IgG respectively. The results obtained show for the first time the occurrence of bacterial antigens, derived from the causative strain, in the synovial fluid in yersinia triggered reactive arthritis.